Social Engineering to Overcome Conflict Between People’s Markets and Supermarkets in Kulon Progo Regency (Review of Regional Regulation No. 16 of 2021) - Wahyu Hidayat; Suryadi Suryadi; Siti Zuliyah (Pandecta Research Law Journal, 2023)
Conflicts between traditional markets, small kiosks owned by individuals, and supermarkets based on modern networked markets are unavoidable, especially at the level of one-sided competition. The Regional Regulation of Kulon Progo Regency Number 16 of 2021 can be a solution in moving the wheels of the economy in the region. Modern shops greatly influence traditional markets or people’s markets and small stalls owned by individuals, which can kill their business. Traditional markets or people’s markets and small stalls are not only the center of people’s economic activities but also a place to make a living for small communities in the Kulon Progo region. The Regional Regulation of Kulon Progo Regency Number 16 of 2021 is intended to protect, empower and organize People’s Markets and structure Shopping Centers and Supermarkets. Protection for people’s markets is carried out by limiting the number of supermarkets and adjusting the distance between traditional markets and shopping centers, and modern shops, the aim is that the existence of people’s markets can be protected from competition that is detrimental to people’s markets, so it becomes a necessity for the Government of Kulon Progo Regency to implement Regional Regulations Kulon Progo Regency Number 16 of 2021 to control the number of supermarkets and provide economic opportunities for people’s markets because this arrangement can overcome conflicts and will provide fifty-fifty benefits as a win-win solution for both so that people’s markets can be saved.